2019
DOI: 10.1111/fwb.13256
|View full text |Cite
|
Sign up to set email alerts
|

Potential anthropogenic regime shifts in three freshwater lakes in Tropical East Asia

Abstract: Regime shifts in ecology are characterised by major, often abrupt changes in ecosystem structure and functioning in response to one or more driving variables, or pressures. Changes in the provision of ecosystem services are a potential outcome. Despite the current combination of rapidly increasing pressures on what are often highly important socio‐ecological systems, the resilience of lakes in the warm tropics to human perturbation is far less well understood than those at higher latitudes. This paper focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 66 publications
1
22
0
Order By: Relevance
“…This coincides with positive mean annual surface air temperature anomalies for Singapore since AD 1985, and is in line with recent warming-related increases in the occurrences of small centric Discostella taxa in lakes located in the Northern Hemisphere (e.g. Rühland and Smol, 2005;Wiltse et al, 2016;Yan et al, 2018) and in a cluster of deep, low-altitude crater lakes in tropical East Asia (Bannister et al, 2019). Nevertheless, given that climate-induced increases in water temperature tend to produce symptoms identical to those created by anthropogenic nutrient enrichment (e.g.…”
Section: Highly Developed State: Effects Of Increasing Transboundary supporting
confidence: 85%
See 1 more Smart Citation
“…This coincides with positive mean annual surface air temperature anomalies for Singapore since AD 1985, and is in line with recent warming-related increases in the occurrences of small centric Discostella taxa in lakes located in the Northern Hemisphere (e.g. Rühland and Smol, 2005;Wiltse et al, 2016;Yan et al, 2018) and in a cluster of deep, low-altitude crater lakes in tropical East Asia (Bannister et al, 2019). Nevertheless, given that climate-induced increases in water temperature tend to produce symptoms identical to those created by anthropogenic nutrient enrichment (e.g.…”
Section: Highly Developed State: Effects Of Increasing Transboundary supporting
confidence: 85%
“…While there is a relatively large body of literature examining the impact of human activities on water bodies at temperate and polar latitudes (Jones et al, 2014; Rühland et al, 2015), effects on the functioning of freshwater ecosystems in the tropics remain poorly understood (Bannister et al, 2019). Freshwater ecosystems in the warm tropics, in particular, are characteristically different from their cooler climate equivalents.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures, especially at levels that one might encounter in Arctic systems, have not been found to be drivers of dissolution. There is extensive literature from temperate and tropical lakes/ponds–diatom profiles recorded in lakes with water temperatures consistently over 25°C (e.g., [ 55 ]), illustrating that elevated temperatures are not in themselves a cause of dissolution. This should be evident to Gajewski, who co-authored a biogeographical study of Arctic diatom assemblages spanning a large temperature gradient from the Boothia Peninsula to northern Ellesmere Island [ 56 ] where it was concluded that “ Diatom concentrations (Conc) are not highly correlated with any measured environmental variable ” including latitude [ 56 ].…”
Section: Criticism 1 Gajewski Questions the Characterization Of Our Sites Into Different Microclimatic Classesmentioning
confidence: 99%
“…In most parts of the country, cases of unregulated aquaculture practices are pretty common, especially in some of the lakes in the province of Laguna (Mendoza et al 2019). Laguna is home to seven neighboring lakes, known as the SML, which are used for both aquaculture and tourism (Brillo 2016a, b;Mendoza et al 2019). Various studies have shown the declining water quality of the lakes brought about by increased nutrient inputs through excess fish feeds and domestic runoffs (Brillo 2015(Brillo , 2016aBannister et al 2019;Mendoza et al 2019;Mendoza-Pascual et al 2021), transforming it into an environment ideal for the propagation of A. dorsalis.…”
Section: Introductionmentioning
confidence: 99%
“…Laguna is home to seven neighboring lakes, known as the SML, which are used for both aquaculture and tourism (Brillo 2016a, b;Mendoza et al 2019). Various studies have shown the declining water quality of the lakes brought about by increased nutrient inputs through excess fish feeds and domestic runoffs (Brillo 2015(Brillo , 2016aBannister et al 2019;Mendoza et al 2019;Mendoza-Pascual et al 2021), transforming it into an environment ideal for the propagation of A. dorsalis. Papa et al (2012) reported that A. dorsalis was the only calanoid species in the SML.…”
Section: Introductionmentioning
confidence: 99%